In‐Situ Early Age Hydration Characterization of LC3 binders - Gómez-de-la-Torre, María de los Ángeles (My University, 2022)
Ha sido una jornada en la que hemos expuesto los logros más importantes del grupo de la UMA "Cement Science Group" en relación a los cementos de arcillas calcinadas. In this workshop, we have exposed the most important achievements of the UMA group "Cement Science Group" related on calcined clay cements.
Keywords: Cemento; Cement hydration; Eco-cement; Calcined clays